Asexuality Associated with Marked Genomic Expansion of Tandemly Repeated rRNA and Histone Genes. (22nd April 2021) - McElroy, Kyle E; Müller, Stefan; Lamatsch, Dunja K; Bankers, Laura; Fields, Peter D; Jalinsky, Joseph R; Sharbrough, Joel; Boore, Jeffrey L; Logsdon, John M; Neiman, Maurine
Abstract: How does asexual reproduction influence genome evolution? Although is it clear that genomic structural variation is common and important in natural populations, we know very little about how one of the most fundamental of eukaryotic traits—mode of genomic inheritance—influences genome structure. We address this question with the New Zealand freshwater snail Potamopyrgus antipodarum, which features multiple separately derived obligately asexual lineages that coexist and compete with otherwise similar sexual lineages. We used whole-genome sequencing reads from a diverse set of sexual and asexual individuals to analyze genomic abundance of a critically important gene family, rDNA (the genes encoding rRNAs), that is notable for dynamic and variable copy number. Our genomic survey of rDNA in P. antipodarum revealed two striking results. First, the core histone and 5S rRNA genes occur between tandem copies of the 18S–5.8S–28S gene cluster, a unique architecture for these crucial gene families. Second, asexual P. antipodarum harbor dramatically more rDNA–histone copies than sexuals, which we validated through molecular and cytogenetic analysis. The repeated expansion of this genomic region in asexual P. antipodarum lineages following distinct transitions to asexuality represents a dramatic genome structural change associated with asexual reproduction—with potential functional consequences related to the loss of sexual reproduction.